Relationship between pre-exercise muscle stiffness and muscle damage induced by eccentric exercise. Issue 4 (21st April 2019) - Xu, Jingfei; Fu, Siu Ngor; Zhou, Dong; Huang, Chen; Hug, François
Abstract: This study aimed to determine whether pre-exercise muscle stiffness is related to the amount of muscle damage induced by an eccentric exercise and to determine whether the post-exercise increase in stiffness is homogenously distributed between the synergist muscles. Fifty healthy participants were randomly assigned to an eccentric exercise group or a control group. The shear modulus (an index of stiffness) of rectus femoris (RF), vastus lateralis (VL) and vastus medialis oblique (VMO) was measured before, immediately after and at 48 h after eccentric exercise. The maximal isometric voluntary knee extension (MVC) torque was also measured. Significant reduction in MVC torque was observed in the eccentric group both at post and 48 H when compared with pre-exercise (both p  < .001). RF shear modulus increased significantly when assessed at 90° of knee flexion at post and 48 H after the eccentric exercise ( p  = .004 and .005, respectively). Slight but significant decrease in VL shear modulus was observed at post-exercise for the eccentric group ( p  = .002). No change was observed in VMO. The decrease in MVC at 48 H was negatively correlated with the RF shear modulus measured at 90° of knee flexion before the exercise. Eccentric exercise induced a wide range of peak torque reduction and muscle-head specific modulation on muscle stiffness. Participants with stiffer RF muscles exhibited greater decrease in force generating capacity at 48 H after eccentric exercise.